Pemberdayaan Ekonomi Kreatif Masyarakat Melalui Pembuatan Dendeng Ikan Layang Di Kelurahan Jambula - Nursanti Abdullah; Eko S.Wibowo; M.Irfan; M.Abjan Fabanjo; Sudirto Malan; Mesrawati Sabar (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Serving fish is one type of fish that has economic value and is included in the resources of small pelagic fish. In North Maluku, Ternate, scad fish are caught using pajeko and bagang fishing gear, the catches obtained by fishermen are directly sold without any processing. Therefore, the activity of empowering the creative economy of the community through training in making scad fish jerky aims to increase knowledge and skills about processing scad fish into products that are durable and quality is maintained and get products that have different flavors. In this activity, the participants came from Jambula Village, District of South Ternate City, which consisted of 25 people and consisted of 3 business groups. The method of carrying out this activity is by practicing surgery, washing, drying, mixing spices and blanching and drying carried out by participants by utilizing the materials provided. The results obtained from this activity are that the participants can master the technology of processing fish into processed products that have different tastes, and can improve the community's economy.